Effect of Baseline Left Ventricular Ejection Fraction on 2-Year Outcomes After Transcatheter Aortic Valve Replacement: Analysis of the PARTNER 2 Trials. (August 2019) - Furer, Ariel; Chen, Shmuel; Redfors, Bjorn; Elmariah, Sammy; Pibarot, Philippe; Herrmann, Howard C.; Hahn, Rebecca T.; Kodali, Susheel; Thourani, Vinod H.; Douglas, Pamela S.; Alu, Maria C.; Fearon, William F.; et al.
Abstract : Background: Impaired left ventricular function is associated with worse prognosis among patients with aortic stenosis treated medically or with surgical aortic valve replacement. It is unclear whether reduced left ventricular ejection fraction (LVEF) is an independent predictor of adverse outcomes after transcatheter aortic valve replacement. Methods and Results: Patients who underwent transcatheter aortic valve replacement in the PARTNER 2 trials (Placement of Aortic Transcatheter Valves) and registries were stratified according to presence of reduced LVEF (<50%) at baseline, and 2-year risk of cardiovascular mortality was compared using Kaplan–Meier methods and multivariable Cox proportional hazards regression. Of 2991 patients, 839 (28%) had reduced LVEF. These patients were younger, more often males, and were more likely to have comorbidities, such as coronary disease, diabetes mellitus, and renal insufficiency. Compared with patients with normal LVEF, patients with low LVEF had higher crude rates of 2-year cardiovascular mortality (19.8% versus 12.0%, P <0.0001) and all-cause mortality (27.4% versus 19.2%, P <0.0001). Mean aortic valve gradient was not associated with clinical outcomes other than heart failure hospitalizations (hazard ratio [HR], 0.99; CI, 0.99–1.00; P =0.03). After multivariable adjustment, patients with reduced versus normal LVEF had significantly higher adjusted risk of cardiovascular death (adjusted HR, 1.42, 95% CI, 1.11–1.81; P =0.005), but not all-cause death (adjusted HR, 1.20; 95% CI, 0.99–1.47; P =0.07). When LVEF was treated as continuous variable, it was associated with increased 2-year risk of both cardiovascular mortality (adjusted HR per 10% decrease in LVEF, 1.16; 95% CI, 1.07–1.27; P =0.0006) and all-cause mortality (adjusted HR, 1.09; 95% CI, 1.01–1.16; P =0.02). Conclusions: In this patient-level pooled analysis of PARTNER 2 patients who underwent transcatheter aortic valve replacement, baseline LVEF was an independent predictor of 2-year cardiovascular mortality. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT01314313, NCT02184442, NCT03222128, and NCT02184441. Abstract : Supplemental Digital Content is available in the text.